Pengaruh Kegiatan Rohani Islam Dan Kedisiplinan Shalat Berjamaah Terhadap Karakter Religius Siswa Madrasah Aliyah Negeri Kota Pekanbaru - Riska Sawitri; Tulai Hahning Safitri; Nur Azizah (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
ABSTRACT This research aims to test influence of islamic spiritual activities and discipline of congregational prayers on the religious character of students at state islamic senior high school in Pekanbaru city. This research is a field research with a quantitative approach, the sample of this research is the students of state Islamic senior high school in Pekanbaru city with a total of 220 students. Data collection techniques using questionnaires and documentation. Data analysis techniques use Linear and Multiple Regression. The results of this research indicate that Islamic Spiritual Activities have a significant influence on the Religious Character of state islamic senior high school in Pekanbaru city. This is indicated by the results of t count greater than t table (64.462 > 0.138) with a sig value. 0.000 < 0.05. With a large contribution of 3%. The discipline of Congregational Prayer has a significant influence on the Religious Character of state islamic senior high school. This is shown by the results of t count greater than t table (0.684 > 0, 138) with a sig. 0.000 < 0.05. With a large contribution of 46.8%. There is a significant influence of Islamic Spiritual Activities and Discipline of Congregational Prayers on the Religious Character of the Students of the state islamic senior high school in Pekanbaru city. This is indicated by the results of the value of f count > f table (97.446 > 0.138). with a large contribution of 53.2%. This means that the contribution of the independent variable to the dependent variable is 53.2%.Copyright © 2018, AL-USWAH. All rights reserved